A preliminary design of an intelligent system for the optimal utilization of renewable energy sources in buildings - Georgiou, Giorgos; Christodoulides, Paul; Kalogirou, Soteris A.; Florides, Georgios A.; Lazari, Lazaros (My University, 2016)
Renewable energy is important nowadays, not only as an environmental scientific issue, but as an obligation with regard to the European regulations. As a result, scientific interest has increased towards the improvement of the different renewable energy technologies and their optimum utilization in different applications. Initially the paper reviews previous studies regarding the optimum utilization and control of the renewable energy generation installed in buildings and in general in building energy management. The final section of the paper is a novel application related to the studies reviewed; however, this application uses a new and simple way to minimize the energy consumption levels through linear programming optimization.
Keywords: Artificial intelligence; Building energy management; Demand side management; Energy policy; Nearly zero energy buildings; Renewable energy resources